2014
DOI: 10.1128/aac.01684-13
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Genes in the Bacteriophage DNA Fraction of Human Fecal Samples

Abstract: A group of antibiotic resistance genes (ARGs) (bla TEM , bla CTX-M-1 , mecA, armA, qnrA, and qnrS) were analyzed by real-time quantitative PCR (qPCR) in bacteriophage DNA isolated from feces from 80 healthy humans. Seventy-seven percent of the samples were positive in phage DNA for one or more ARGs. bla TEM , qnrA, and, bla CTX-M-1 were the most abundant, and armA, qnrS, and mecA were less prevalent. Free bacteriophages carrying ARGs may contribute to the mobilization of ARGs in intra-and extraintestinal envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 32 publications
2
66
0
2
Order By: Relevance
“…β-Lactamases were closely inspected, as several reports have suggested their presence on phages (Quiros et al, 2014;Asare et al, 2015a), sometimes with atypical length. Indeed, one such protein annotated as a β-lactamase is, in fact, a tail fiber protein (Cresawn et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…β-Lactamases were closely inspected, as several reports have suggested their presence on phages (Quiros et al, 2014;Asare et al, 2015a), sometimes with atypical length. Indeed, one such protein annotated as a β-lactamase is, in fact, a tail fiber protein (Cresawn et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In the same vein, a longitudinal metagenomic analysis investigating the composition and dynamics of the human gut virome (including eukaryotic viruses and phages) revealed that in addition to complete or partial bacteriophage genomes, most of the DNA contigs encoded gene products of unexpected functions, such as those of viral CRISPR arrays and antibiotic resistances [26]. Finally, analysis of the packaged DNA from the feces of healthy humans revealed the presence of antibiotic resistance genes, bla TEM , bla CTX-M-1 , mecA, armA, qnrA, and qnrS in 77 out 80 samples analysed [27 ]. These findings suggest that phages are involved in the spread of antibiotic resistance and highlight the importance of transduction in the emergence of novel virulent clones.…”
Section: Transfer Of Bacterial Virulence Genesmentioning
confidence: 97%
“…Regarding the implementation of these techniques for routine diagnosis of pathogens, the interference that phages could cause in the assembly of a genome sequence should be considered when DNA is obtained directly from the samples and not from isolates, particularly from the less abundant members of a microbial community (40). For example, virulence genes (stx or others) or antibiotic resistance genes, both reported in phages or phage-like elements (41)(42)(43), will certainly be detected, but the strain or species to which they belong, if any, will be unknown. The reduction of possible interferences would improve the efficiency and reliability of genomics when routinely applied.…”
Section: Pbsmentioning
confidence: 99%